Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/2515690x19876599
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Meditation Versus Progressive Relaxation Meditation: Impact on Chronic Pain in Older Female Patients With Diabetic Neuropathy

Abstract: Chronic pain, the most common complication of diabetes, is treated with medication often to no avail. Our study aimed to compare the use of mindfulness meditation and progressive relaxation to reduce chronic pain in older females with diabetes. Methods The 105 study participants were divided randomly into 3 groups: Group MM (mindfulness meditation), Group CM (control meditation), and Group PM (progressive relaxation meditation). Assessment of analgesic effectiveness required changes in average daily pain Brief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 54 publications
(59 reference statements)
1
22
1
5
Order By: Relevance
“…In accordance with our first hypothesis, both progressive muscle relaxation and mindfulness meditation reduced the severity of DPNP. Hussain and Said (2019) evaluated the effects of progressive muscle relaxation and mindfulness meditation on neuropathic pain severity in patients with type 2 diabetes and reported results similar to those of our study. Earlier studies addressing the effects of progressive muscle relaxation in different chronic pain conditions (including neck or back pain and fibromyalgia) also supported the pain‐relieving effect of progressive muscle relaxation (Coppieters et al, 2016; Lauche et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In accordance with our first hypothesis, both progressive muscle relaxation and mindfulness meditation reduced the severity of DPNP. Hussain and Said (2019) evaluated the effects of progressive muscle relaxation and mindfulness meditation on neuropathic pain severity in patients with type 2 diabetes and reported results similar to those of our study. Earlier studies addressing the effects of progressive muscle relaxation in different chronic pain conditions (including neck or back pain and fibromyalgia) also supported the pain‐relieving effect of progressive muscle relaxation (Coppieters et al, 2016; Lauche et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
“…To date, numerous studies have examined the effects of different pharmacological and nonpharmacological approaches on diabetic peripheral neuropathic pain. Among these studies, reduction in pain scores varying between 0.6 and 4.5 points had been considered clinically meaningful (Arezzo, Rosenstock, LaMoreaux, & Pauer, 2008; Gok Metin, Arikan Donmez, Izgu, Ozdemir, & Arslan, 2017; Hussain & Said, 2019; Nathan et al, 2017). Although the types of interventions, durations of interventions, and follow‐up periods differed in these reports, the reduction in pain scores in this study is comparable to those of the above‐mentioned reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies reported patients with DN pain, type 2 DM, VAS pain score of 4.83, pain duration of 6 to 12 years (Asadi et al, 2019). Most samples were 105 (Hussain & Said, 2019), with an average age of 59 years and 544 (64%) with the female gender.…”
Section: Characteristics Of the Cam Intervention Sample On Dn Painmentioning
confidence: 99%